Readiness of Teachers for Developing Interaction with Children - Silakova M.M; Zakharova L.M (Moscow State University of Psychology and Education, 2019)
The article discusses the concept of "the teacher's readiness for developing interaction," which is regarded as a professional personality quality associated with the uniqueness of each child. It is also characterized by the ability of a teacher to provide subjective interaction with a child, to support the development of children's initiative, to design skills for the individual space of the child's personal development, to form personal qualities that ensure the emotional well-being of each child. The article provides the data on the level of readiness of educators to implement developing interaction with preschool children. The implementation of the developing interaction largely depends on the style of pedagogical communication, the chosen position in communication: Adult, Parent or Child (E. Berne) and the level of emotional intelligence development of the educators. Analysis of the study results showed that all educators have the first and second levels of effectiveness of pedagogical communication, characterized by particular skills in the organization of children. The majority of educators while communicating prefer the ego position of "Adult" with the formula A-P-Ch, and most educators have a low level of integrative emotional intelligence and empathy, which does not contribute to the development of interaction with children. The results of the diagnosis showed the need to strengthen not only the practical component of the teachers 'professional readiness, but also the concretization of students' ideas about the developing nature of interaction, as well as the identification of the benefits of traditional types of children's activities in the development of children's interest and initiative.